1-Decyloxy-4-nitrobenzene - Yue, Xi-Gui (International Union of Crystallography, 2009)
The title compound, C(16)H(25)NO(3), has a zigzag decyloxy chain para to the nitro group of the aromatic ring. There are two independent molecules; the two rings are aligned at 48.15 (7)°. In the crystal, weak C—H⋯O hydrogen bonds lead to the formation of infinite chains.